2021
DOI: 10.1021/jacsau.1c00270
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Amino Sugar-Based Supramolecular Hydrogelator with Reduction Responsiveness

Abstract: Stimuli-responsive supramolecular hydrogels are a newly emerging class of aqueous soft materials with a wide variety of bioapplications. Here we report a reduction-responsive supramolecular hydrogel constructed from a markedly simple low-molecular-weight hydrogelator, which is developed on the basis of modular molecular design containing a hydrophilic amino sugar and a reduction-responsive nitrophenyl group. The hydrogel formation ability differs significantly between glucosamine- and galactosamine-based self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…In addition, solution exchange without pH shift resulted in no accumulation of FA along fibrous morphology, most probably due to low ligation efficiency under rather alkaline pH 8.0 (Figure S6). Overall, these results clearly demonstrate that the in situ fabricated supramolecular nanofiber network consisting mainly of NPmoc−FF−NHNH 2 in hydrogel state can be decorated with an aldehyde‐appended molecule by post‐assembly modification [3,16h] …”
Section: Resultsmentioning
confidence: 52%
“…In addition, solution exchange without pH shift resulted in no accumulation of FA along fibrous morphology, most probably due to low ligation efficiency under rather alkaline pH 8.0 (Figure S6). Overall, these results clearly demonstrate that the in situ fabricated supramolecular nanofiber network consisting mainly of NPmoc−FF−NHNH 2 in hydrogel state can be decorated with an aldehyde‐appended molecule by post‐assembly modification [3,16h] …”
Section: Resultsmentioning
confidence: 52%
“…48 GlcN-NPmoc, an amino sugar-based supramolecular hydrogelator can also gel water at concentrations as low as 0.75 wt%. 49 The 1 : 1.5 R-11-3-DA : SL mixed system was the first example of low molecular weight gels formed by typical surfactants mixed at low concentrations. At higher concentrations, the solutions showed obvious blue opalescence, indicating the presence of aggregates with hydrodynamic diameters of several hundred nanometers.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that not only expanding the range of biomolecules applicable to the molecular-design strategy for the construction of reductionresponsive biomolecules with desired functions, but also improving and adaptively modulating sensitivity to bio-related reduction stimuli [40] is a critical issue to address for future and on-going bioapplications. [34] A molecular model of the self-assembled structure in the stick model is shown. Red = Na 2 S 2 O 4 in HEPES buffer (pH 7.4).…”
Section: Discussionmentioning
confidence: 99%
“…[33] We recently found that the introduction of the NPmoc group into glucosamine (GlcNH 2 ) allowed for the development of one of the simplest supramolecular hydrogelators (GlcN-NPmoc, Figure 11), capable of showing reduced responsiveness. [34] Similarly to the aforementioned peptide-based hydrogelators, a Fmoc-introduced GlcN (namely, GlcN-Fmoc) was found as a supramolecular hydrogelator [35] in advance of GlcN-NPmoc. Nevertheless, an intriguing difference, in addition to the reduction-responsiveness, might be the fact that GlcN-NPmoc is a hydrogelator but GalN-NPmoc, consisting of galactosamine (GalNH 2 ), is not, whereas both GlcN-Fmoc and GalN-Fmoc are hydrogelators.…”
Section: Saccharidesmentioning
confidence: 93%
See 1 more Smart Citation